Simulasi Kinematika Interaktif (Studi Kasus: Balai Diklat Metrologi) - Erwin Yulianto; KM. Syarif Haryana (Jurnal Computech & Bisnis (e-Journal), 2016)
One of the problems that exist at Metrology Training Center is the lack of teaching materials that can increase student interest in the field of measurement / calibration. Additionally, another difficulties that come from the students to learning the concepts of physics especially kinematics is a lack of understanding of mathematical modeling and simulation model depiction form a case studies. This research is expected to help resolve those difficulties by making the software as a interactive teaching materials supplement, so it can add to the interest of students to learning physics generally and calibration in the field of kinematics in particular. Interactive Kinematics Simulation Applications equipped with teaching materials supplement which implemented into simulation model. Based on the questionnaires results, turned out that these applications can increase the attractiveness of the students to calibration material especially in the field of kinematics. In addition, the application can be used as a teaching materials supplement.Keywords: Physics, Kinematics, Simulation, Teaching Material Supplements